2019
DOI: 10.1021/acs.jpcb.9b04029
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Inversion of Amino Acids in Antiparallel β-Sheets at Interfaces Probed by Vibrational Sum Frequency Generation Spectroscopy

Abstract: A parallel study of protein variants with all (L-), all (D-), or mixed (L-)/(D-) amino acids can be used to assess how backbone architecture versus side chain identity determines protein structure. Here, we investigate the secondary structure and side chain orientation dynamics of the antiparallel β-sheet peptide LK 7 β (Ac-Leu-Lys-Leu-Lys-Leu-Lys-Leu-NH 2 ) composed of all (L-), all (D-), or alternating (L-Leu)/(D-Lys) amino acids. Using interface-selective vibrational sum frequency generation spectroscopy (V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 85 publications
5
33
0
Order By: Relevance
“…Therefore, in the folded peptide LK 7 β, the chirality of the C α -H group controls the chirality of the N-H group. Since the LK 7 β peptide with mixed L-and D-amino acids does not fold as recently reported 27,35 and in our own measurement, such one-on-one chiral correspondence between the C α -H group chirality and the N-H chirality in the folded peptide LK 7 β suggests deep connections in the structure of the amino-acids chirality to the chiral structure of folded peptides and proteins. Further studies in this direction may provide clues on understanding of the basic architecture of the folded protein, protein folding processes and the questions of the origin of life.…”
supporting
confidence: 82%
“…Therefore, in the folded peptide LK 7 β, the chirality of the C α -H group controls the chirality of the N-H group. Since the LK 7 β peptide with mixed L-and D-amino acids does not fold as recently reported 27,35 and in our own measurement, such one-on-one chiral correspondence between the C α -H group chirality and the N-H chirality in the folded peptide LK 7 β suggests deep connections in the structure of the amino-acids chirality to the chiral structure of folded peptides and proteins. Further studies in this direction may provide clues on understanding of the basic architecture of the folded protein, protein folding processes and the questions of the origin of life.…”
supporting
confidence: 82%
“…To gain further insights about the hydration structure around LK 7 β, we performed MD simulations and hydrogen-bond analyses (see Materials and Methods and SI Appendix). LK 7 β was modeled as a protein composed of five β-strands at the vacuum-water interface, as previously reported (11). The MD simulations confirmed that the amphiphilic LK 7 β adopts a stable pleated, antiparallel β-sheet structure (SI Appendix, Figs.…”
supporting
confidence: 59%
“…1 A, Top) of (L-) LK 7 β is centered at 1,620 cm −1 , indicating the formation of antiparallel β-sheet structures. Previously, we showed that the homodyne chiral SFG signal vanishes when the pH of the sample is lowered to ∼2, which denatures the antiparallel β-sheets, or when the LK 7 β peptide is composed of (L-) leucine and (D-) lysine, which disrupts β-sheet formation (11). These experiments demonstrated that the chiral SFG response originates from the folded β-sheet secondary structure.…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations